Speed estimation for a capacitor drive induction coil launcher - Yazdi, Seyed Ali Miratashi (2012)
The essential concept of the Capacitor drive traveling wave linear induction coil launcher is based on the principal of the classical linear induction electric machines. The literatures present the model of the launcher based on the circuits equations. The equations describe the currents and voltages of the coils and capacitors bank and interactive force between the coils in every time step of launching. The main launcher power components are drive and projectile coils, capacitor bank and thyristors.The resistances of the coils and their changes due to the temperature have been considered in the previous research but for pure copper and aluminum. The characteristics of the capacitors and thyristors have not been considered because the capacitors and thyristors resistances are so smaller than coils resistance, and have been neglected in previous research. The thyristors have simple characteristics and have small voltage drop and power loss but there are many different kinds of capacitors in the market and each model have different resistance and thermal specifications. A simulation program was coded to determine output velocity of the projectile and other important parameters of the launcher in terms of inputs. The inputs are mass of the projectile, temperature of the launcher components and capacitors bank voltages. The model equations have been improved by considering the temperature characteristics of the capacitors and coils with impure copper and aluminum. The curve fittings method has been used for extracting the equation from the capacitors datasheets. The results show that the coils resistance have very important role in launcher performance. So they have to be calculated precisely and added to the model. The differences between simulation model outputs with considering capacitors and thyristors characteristics and without considering them are so small and this confirmed previous research. In practical applications, one of the basic necessities of the every launcher is to determine the muzzle speed before shooting in short period of time. Therefore, there is a need to estimate initial voltage of the capacitors bank to reach the desired muzzle speed. There is a lack of a method that could estimate the initial voltage of the capacitors bank for specific muzzle speed. So a new system needed with the following inputs, the temperature of projectile, the mass of the projectile, the desired speed and the output is the capacitors bank voltage. In fact, a speed estimator is required to calculate proper input capacitors voltage in order to reach the desired muzzle speed. A novel method was applied by using intelligent systems for speed estimation and the results have been verified by the prototype launcher. In this research the temperature effect on each parts of the launcher tested separately and it was verified that for the small size launchers the coils have the important role in temperature effect on the launcher performance and capacitors have not considerable role. Also the speed estimator model is a new application of neural network based systems and the test results approved that is a powerful tool for improving the launcher capabilities.